Asymmetric total synthesis of (+)-dihydroitomanallene B and formal synthesis of (−)-kumausallene. Issue 85 (5th October 2022) - Fernandes, Rodney A.; Kumar, Atul; Pathare, Ramdas S.
Abstract : The first total synthesis of (+)-dihydroitomanallene B and its two diastereomers, and the formal synthesis of (−)-kumausallene from a common intermediate based on protecting-group-directed Tsuji–Trost cyclization of allyl acetates are reported. Abstract : The first asymmetric total synthesis of (+)-dihydroitomanallene B and its two diastereomers, and the formal synthesis of (−)-kumausallene are reported. The synthesis of the former was completed in 18 steps from 1, 4-butanediol (3.4% overall yield), with diastereoselective Tsuji–Trost cyclization to access cis -2, 5-disubstituted-3-oxygenated THF scaffold and a Corey–White–Posner reaction to install the bromoallene moiety as the key steps. In addition, the enantioselective formal total synthesis of (−)-kumausallene involving the key Tsuji–Trost cyclization is also realized.